THE LEVEL OF EFFECTIVENESS OF UNITY GOVERNMENT IN MALAYSIA - Aznan, Adam Haziq; Ridzuan, Abdul Rauf; Mohd Shamsul Amri, Ahmad Luqman; Mohd Hamim, Muhammad Adib Farhan; Mustazar, Muhammad Aiman Daniel; Djuyandi, Yusa; Abdul Wahab, Shafezah; Zulhkaim Zailani, Muhammad Hafiez (I-iECONS e-proceedings, 2023)
Malaysia is a multicultural country that aspires to do great things economically. Dato' Seri Anwar Ibrahim, prime minister of Malaysia since 2022, has been active in efforts to strengthen national unity and develop the country. This research aims to determine the effectiveness of a unity government, which consists of two different political views and parties. Despite the success of the unity government from the previous PRU, the majority of Malaysians still doubt the effectiveness of the new government due to different perspectives and objectives from each political party. Raosoft's Sample Size Calculator was used to establish a minimal necessary sample size. The research is quantitative in nature and was conducted using the Google Forms platform with the participation of 300. Based on the findings, the level of effectiveness towards unity government is high (M=2.98), and based on the data presented, the level of understanding towards Malaysia MADANI is also high (M=2.81).